Teachers' perceptions of professional identity and communities of practice - Sadek, Heidi Mohamed Badr El-Din (AUC Knowledge Fountain, 2020)
This study investigates the perceptions of English instructors on their professional identities, within private higher education institutions. The aim of the current study is to explore the perceptions of teachers' professional identities and the aspects that affect it, as well as, their perceptions of communities of practice and its effect on their professional identity. The study is conducted on 26 English instructors, who teach Academic English in private institutions. A qualitative approach is utilized and individual interviews, and focus group interviews were conducted with all the participants. Findings show that there are four main aspects that shape and affect a teacher's professional identity, such as teacher role, appreciation and connection, competence and self-efficacy, and future trajectories. These aspects seem to highly affect the instructors' professional identity in a positive way. Moreover, the teachers are aware of the significance of self-reflection and professional improvement. Furthermore, there is an indication that membership in communities of practice is a crucial action in order to improve teachers' teaching skills, share common experiences and enhance social learning (Wenger, 1998). In addition, participants believe that it is a method for developing their performance to enhance their students' academic learning. Data also shows that it has a positive effect on teachers' professional identities. The study suggests some practical implications that could assist teacher educators, and if applied in teacher education programs and trainings could help in supporting and developing their professional identities.